syntheses of news antimalaria and antitoxoplasmosis compounds. - (:unkn) unknown (My University, 2012)
Malaria is the more deadly parasitic disease, affecting 3.3 billion people (half of the world population). In 2010, the number of deaths due to malaria was estimated at 655,000, of which 91% of cases for the African continent. Pregnant women and children under 5 years (86% of deaths) are the most vulnerable. For African countries, malaria is not only a disease due to poverty, it is also the cause of the poverty. Due to this serious problem, it is urgent to find new effective treatments accessible to affected populations. Toxoplasmosis is a parasitic disease that affects mainly the industrialized countries (50% of the French population). This parasitosis is termed opportunistic disease because it can be dangerous for pregnant women and immunocompromised patients (people with AIDS or who have undergone organ transplantion). Parasites responsible of malaria (P. falciparum) and toxoplasmosis (T. gondii) belong to the same family of apicomplexan, which are unicellular organisms. To develop new antimalarial and antitoxoplasmosis compounds, we found inspiration from natural products: aculeatins and cyclopeptides analogue of FR235222. To optimize antiparasitic properties of these natural products, we have developed short synthetic methods. New analogues of aculeatin were obtained by using an approach involving cascade and tandem phenolic oxidative reactions, induced by hypervalent iodine (III) reagents. Radical chemistry with xanthates and thioesters allowed us to obtain a great diversity of cyclopeptides analogue of FR235222. The antiparasitic activities of various analogs obtained were evaluated, and some has reached nanomolar efficacy.STAR
Keywords: African Research